2022
DOI: 10.1007/s10803-022-05622-y
|View full text |Cite
|
Sign up to set email alerts
|

‘They ask no questions and pass no criticism’: A mixed-methods study exploring pet ownership in autism

Abstract: Many autistic people cite a strong attachment to animals, and some studies suggest they may even show a bias towards animals over people. This mixed-methods study explored companion animal attachment in the adult autistic community. In a quantitative study with 735 people, we found that autistic adults were equally attached to their pets as neurotypicals but were less likely to own them, even though pet ownership corresponded with better mental health outcomes. Substituting pets for people also served as a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…This continued development may explain why studies on very young autistic children show impaired performance in both human and nonhuman face recognition (Chawarska & Volkmar, 2007), while studies on older autistic children, adolescents and adults show an intact or even relatively enhanced ability for nonhuman performance (for a review, see . Autism research is rife with studies showing that autistic people enjoy engaging with the nonhuman and may be doing so increasingly throughout development, whether it be through animation (Holmgaard et al, 2013), contact with pets (Atherton et al, 2022), animal-assisted therapy (O'Haire, 2013, or even embodying the nonhuman during online game-play (Stendal & Balandin, 2015) (for a review, see . This type of engagement may allow autistic people to develop social expertise and derive social pleasure in ways that do not rely on human specialization, which may function as an extension of how autistic people begin to see themselves as more than human (Davidson & Smith, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This continued development may explain why studies on very young autistic children show impaired performance in both human and nonhuman face recognition (Chawarska & Volkmar, 2007), while studies on older autistic children, adolescents and adults show an intact or even relatively enhanced ability for nonhuman performance (for a review, see . Autism research is rife with studies showing that autistic people enjoy engaging with the nonhuman and may be doing so increasingly throughout development, whether it be through animation (Holmgaard et al, 2013), contact with pets (Atherton et al, 2022), animal-assisted therapy (O'Haire, 2013, or even embodying the nonhuman during online game-play (Stendal & Balandin, 2015) (for a review, see . This type of engagement may allow autistic people to develop social expertise and derive social pleasure in ways that do not rely on human specialization, which may function as an extension of how autistic people begin to see themselves as more than human (Davidson & Smith, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Autism research is rife with studies showing that autistic people enjoy engaging with the nonhuman and may be doing so increasingly throughout development, whether it be through animation (Holmgaard et al, 2013), contact with pets (Atherton et al, 2022), animal‐assisted therapy (O'Haire, 2013), or even embodying the nonhuman during online game‐play (Stendal & Balandin, 2015) (for a review, see Atherton & Cross, 2018). This type of engagement may allow autistic people to develop social expertise and derive social pleasure in ways that do not rely on human specialization, which may function as an extension of how autistic people begin to see themselves as more than human (Davidson & Smith, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesize that those on the spectrum anthropomorphise their pets in line with neurotypicals and may show evidence of increased anthropomorphism out of a need for non-traditional social outlets (as suggested by Atherton et al, 2022). An intact or even increased tendency to anthropomorphise pets would further support research on animal companionship that suggests pet ownership serves an important social function for those on the spectrum.…”
Section: Introductionmentioning
confidence: 96%
“…Qualitative research on the autism-animal bond describes people whose joys in life are made possible through the bond with their pets (Malcolm et al, 2017;Solomon, 2010). Furthermore, recent work by Atherton et al (2022) showed that not only are autistic individuals just as likely attached to their pets, but pet ownership also corresponded with improved mental health and social outcomes.…”
Section: Introductionmentioning
confidence: 99%